Management of Man-made forests in India - Maslekar, A. R. (Indian Forester, 1985)
Natural forests of India have been under pressure particularly since the Independence. Recent studies indicate that the country may not have even 10% of the land under forests. The widening gap between supply and demand of the forest products can only be met through undertaking extensive as well as intensive man-made plantation efforts. Almost a million hectares have come under such plantation in the last decade, particularly after the publication of the "Interim Report of the National Commission on Agriculture Man-made Forestry" in 1972 and establishment of Forest Development Corporations in different States. The plantations created so far have given very valuable experience and one is now able to plan in a better manner for the future. This article indicates the salient experiences gained and makes suitable suggestions for the future management of man-made forests in the country.